Therapeutic responses to quinine and clindamycin in multidrug-resistant falciparum malaria. - Pukrittayakamee, S; Chantra, A; Vanijanonta, S; Clemens, R; Looareesuwan, S; White, N (2000)
Therapeutic responses to clindamycin in combination with quinine were assessed in adult Thai patients with uncomplicated multidrug-resistant Plasmodium falciparum malaria. In total 204 patients were randomized to receive a 7-day oral treatment regimen of quinine (Q(7)) either alone (n = 68), in combination with clindamycin (Q(7)C(7); n = 68), or in combination with tetracycline (Q(7)T(7); n = 68). All patients had uncomplicated recoveries with no serious adverse effects. Fever clearance times for both of the two combination regimens (median of 47 h and range of 8 to 120 h for Q(7)C(7) and median of 36 h and range of 8 to 117 h for Q(7)T(7)) were significantly shorter than that for the Q(7)-only regimen (median, 56; range, 4 to 152 h) (P = 0.002). Parasite clearance times (overall mean +/- standard deviation, 78 +/- 23 h) were not significantly different between the three treatment groups (P = 0. 98). The cure rates assessed at 28 days of follow-up were 100% for Q(7)C(7) and 98% for Q(7)T(7), whereas the cure rate was 87% for the Q(7)-only regimen (P < or = 0.04). Clindamycin in combination with quinine is a safe and effective treatment for multidrug-resistant P. falciparum malaria. This combination may be of particular value in children and pregnant women, in whom tetracyclines are contraindicated.